Transcriptome Analysis of Rat Lungs Exposed to Moxa Smoke after Acute Toxicity Testing. (18th December 2021) - Xu, Xiaoyu; Deng, Wen; Zhang, Wanqing; Zhang, Junhua; Wang, Muchen; Shan, Si; Liu, Hongning
Abstract : The increasing use of moxibustion has led to a debate concerning the safety of this treatment in human patients. Inhalation of cigarette smoke induces lung inflammation and granulomas, the proliferation of alveolar epithelial cells, and other toxic effects; therefore, it is important to assess the influence of inhaled moxa smoke on the lungs. In the present study, a novel poisoning cabinet was designed and used to assess the acute toxicity of moxa smoke in rats. We evaluated pathological changes in rat lung tissue and analyzed differentially expressed genes (DEGs) using RNA-seq and transcriptomic analyses. Our results show that the maximum tolerable dose of moxa smoke was 290.036 g/m³ and LC50 was 537.65 g/m³. Compared with that of the control group, the degree of inflammatory cell infiltration in the lung tissues of group A rats (all dead group) was increased, while that in group E rats (all live group) remained unchanged. GO and KEGG enrichment analyses showed that the DEGs implicated in cell components, binding, and cancer were significantly enriched in the experimental groups compared with the profile of the control group. The expressions of MAFF, HSPA1B, HSPA1A, AOC1, and MX2 determined using quantitative real-time PCR were similar to those determined using RNA-seq, confirming the reliability of RNA-seq data. Overall, our results provide a basis for future evaluations of moxibustion safety and the development of moxibustion-based technology.